Comparative Study of Kuttab Islamic Education System and Madrasah Ibtidayah Education System - Muhtar, Fathurrahman (SYAMIL: Journal of Islamic Education, 2021)
This article shows the numerous benefits created in the 7th-13th century A.D. by a primary education institution named Kuttab. Kuttab is an educational institution that teaches the Qur'an to be read and memorized, history to be studied, and Arabic verses. This article utilizes an approach to literature research, gathering different references related to Kuttab. The empirical content process then evaluates the relation, and conclusions are drawn from the reference analysis. This paper concludes that with education in Madrasah Ibtidaiyah, Kuttab institutions have a similar curriculum. The excellence of Kuttab focuses more on memorizing the Qur'an so that in the golden age (7-12 years), Kuttab students will remember the entire material of the Qur'an, in addition to teachers who have excelled and skills. Unlike Ibtidaiyah madrasahs, which do not focus students on memorizing the Qur'an, and as teachers in Kuttab, teachers are also far from professionalism. In comparison to the current madrasah Ibtidaiyah curriculum, the learning materials in Kuttab are thin.Keywords : curriculum, kuttab, madrasah, teacher, student.